Cardiopulmonary Resuscitation in Congenital and Acquired Heart Disease. (August 2016) - Tabbutt, Sarah; Marino, Bradley S.
Abstract : Objectives: The Pediatric Advanced Life Support recommendations were developed for otherwise healthy infants and children with normal cardiac anatomy. Patients with acquired and congenital heart disease require specific considerations that may differ from the Pediatric Advanced Life Support recommendations. Our aim is to present prearrest, arrest, and postarrest considerations that are unique to children with congenital and acquired heart disease. Data Source: MEDLINE and PubMed. Conclusion: A clear understanding of the underlying anatomy and physiology of congenital and acquired heart disease is imperative in order to employ the appropriate modifications to the current Pediatric Advanced Life Support recommendations and to optimize outcomes.